Children’s literature and geometry: possible connections mapped by the state of knowledge (Research, Society and Development, 2020)
This paper aims to present an excerpt, from an initial study, of a bibliographic dissertation, which put into discussion the development of topological relations, according to Piaget, in the construction of space by the child, from an interlocution with children's literature. With the intention of sharing with the teachers of the early school years the idea of exploring children's literature as an ally for the teaching of mathematics, this study aimed to develop didactic sequences that favored the development of topological dimensions, from the moments of storytelling. The interrelationship of children's literature with geometry, defended here as didactic potential, permeates the entire text and inserts research in the field of mathematical education. The construction of the state of knowledge showed that few studies have been done on this theme and, even less, with regard to topological relationships, which can be explored from children's stories. This result points to the need to broaden the field of research on children's literature and the teaching of geometry, showing that, from reading and analyzing the investigated productions, storytelling presents itself as a pedagogical resource to be explored as potential for teaching Mathematical Education, which the dissertation ended up contemplating in its writing, and which was socialized with the other researchers in the elaboration of an activity notebook with didactic sequences created from excerpts from “As aventuras do avião vermelho”, by Erico Veríssimo.Incluir o resumo em inglês.